INOVASI SISTEM INFORMASI QUICK RESPONSE (SIQUPON) DI DINAS PERHUBUNGAN KOTA PEKALONGAN - Ita Eliza Choirunnisak; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Public service is a strategic issue to be discussed, because it deals with meeting the growing needs of the community along with the development of Science and Technology. The government as a public service provider is required to continue to improve the quality of services to the community. One way to achieve this is by innovating public services. The Quick Response Information System (SIQUPON) is an innovation that is implemented in the Department of Transportation of Pekalongan City. SIQUPON functions as an information and coordination center to overcome traffic problems. However, in its implementation SIQUPON has not been able to run optimally. The purpose of this study was to analyze the Quick Response Information System Innovation (SIQUPON) at the Pekalongan City Transportation Agency. The research method used is descriptive qualitative by analyzing using 5 attributes of innovation which include real benefits, suitability, complexity, possibility of trying, observing and analyzing supporting and inhibiting factors. Supporting factors for SIQUPON's innovations include the desire to change, openness to aspirations, and the existence of responsible parties. The inhibiting factors include the absence of special budget planning, dependence on certain figures, the absence of awards or incentives. Suggestions that can be given include SIQUPON budgeting, renewal of the structure and clear division of tasks towards SIQUPON managers, increasing work motivation through awards and incentives, applying democratic leadership styles, branding the public about the importance of carrying out orderly traffic and use of SIQUPON through social media media.